(untitled) (Third Sector Social Economic Review, 2017)
In recent years the decentralized approach expressed in the concept of ""local development"" has begun to take more lives in Turkey with the regional development agencies and the regulation which is known as the ""Whole-city Law"" which entered into force in 2014. After the Whole-city Law, the settlement units that were previously in the village legal entity were transformed into the neighborhood status. With this regulation, regions that have become neighborhoods but have rural settlement characteristics have become areas in which local governments are obliged to provide services. One of the most important characteristics that characterize rural areas is that the economy is predominantly depends on agricultural. Therefore, besides many municipal services, the issue of local governments to deliver some agricultural services to the rural areas in the neighborhood status has come to the agenda after 2014. İzmir Metropolitan Municipality carries out its activities for agriculture and rural development under the presidency of Agricultural Services Department. Cooperatives play an important role in activities for agriculture and rural development by local governments in İzmir. In this respect, İzmir was considered as an example to be examined in terms of local government-cooperative cooperation. In this framework, cooperation of local governments and producer organizations has been been examined in detail. Problems encountered during the cooperation process has been revealed and the on which basis the process can be made more sustainable has been investigated.